A Landmark in the History of Catholic Social Thought in the Province (Relations industrielles / Industrial Relations, 1950)
The joint pastoral letter of the bishops of Quebec on "the labour problem in the light of the social doctrine of the Church" is a document which will mark an epoch in the history of Catholic social thought in this province. Covering nearly eighty pages and more than two hundred paragraphs, it is a masterly adaptation of the traditional teaching of the Church to the particular conditions of the province of Quebec. It serenely calls to mind the demands of truth and justice and invites all tocollaborate in the Christian reconstruction of the working world.